Comprehensive Hip Fracture Care Program: Successive Implementation in 3 Hospitals. (14th May 2019) - Jackson, Kelly; Bachhuber, Mary; Bowden, Dawn; Etter, Katherine; Tong, Cindy
Introduction: Hip fractures are common and costly in the elderly population, often contributing to loss of function and independence. Prompt, coordinated surgical care may improve clinical and economic outcomes for this population. Materials and Methods: We created an interdisciplinary care program focused on minimizing time spent immobilized awaiting surgery and streamlining the care pathway for hip fracture. Patients older than 65 years with any hip fracture type including hip fracture repair Diagnosis-Related Group codes (MS-DRG 480, 481, or 482) and MS-DRG 469 and 470 with a hip fracture diagnosis were included in the study. The Hip Fracture Care program (HFCP) was implemented on a staggered basis in 3 hospitals in the HonorHealth system. Time to surgery, length of stay, and discharge location (home/skilled nursing facility) were compared pre- and post-intervention, utilizing an interrupted time series analysis to account for background trends. Results: More than 2000 patients across the 3 facilities received HFCP care; demographics were similar for the 826 patients serving as the pre-implementation comparison group. Mean (standard deviation [SD]) length of stay decreased from 5.6 (4.0) to 4.7 (2.9) days (mean difference 0.9 days; P < .05). Mean (SD) time from admission to the operating room decreased from 30.8 (21.1) to 25.6 (20.5) hours (mean difference 5.2 hours; P < .05). There was no change in the proportion of patients discharged to home versus skilled nursing facility. Discussion: Optimal care of this vulnerable population can significantly reduce the time to surgery and length of stay. Conclusions: Length of stay was reduced by nearly 1 day with implementation of a multifactorial program for hip fracture care.